Use Of Microsoft Teams Add-Ons in High Schools: The Effect on Student Learning Outcomes - Sanjaya Pinem; Viktor Edison Hutagaol (INFOKUM, 2021)
Online learning is an essential thing during the covid-19 pandemic. Especially the education sector, whereas almost everything must be put on the online system. Online learning implementation can harm the achievement of student learning outcomes. The SMA Katholik 2 Kabanjahe experienced a decline in their learning outcomes using online learning, far below the standard built from minimum competence for the test scores of mathematics subjects. This study aims to increase student learning outcomes with optimized Microsoft Teams Add-ons in mathematics subjects based on these problems. The type of this research is Classroom Action Research, and the subject of this research is students class X SMA Katholik 2 Kabanjahe with 21 students as participants. Observation student evaluation, an evaluation test, and a questionnaire are used to collect data. The result has shown that students' learning outcomes were significantly improved from the first cycle by 42.85% on average increased to 72.16% in the second cycle. Student's activity also significantly changed from the first cycle by 32.14%, increasing to 72.00% on average from the second cycle. 79.87 % of students gave positive responses and 20.13% for negative responses.